AGENT-BASED GRID COMPUTING LOAD BALANCING ATAPPLICATION LEVEL - Abdul Mohsin, Husam; Harif, Alaa (Iraqi Journal of Science, 2024)
AbstractGrids functionally combine globally distributed computers and informationsystems for creating a universal source of computing power and information. Grid isa very large scale, generalized distributed network computing system that can scaleto Internet-size environments with machines distributed across multipleorganizations and administrative domains. The emergence of new varietyapplications demand that Grids support compatible efficient data and resourcemanagement mechanisms, This paper provides an application level load balancingfor individual parallel jobs for grids data, implemented by using Borland JBuilder 7Enterprise - WebLogic Edition.